Antara Hasrat dan Privasi Diri: Anonimitas Penggemar Cerita Alternative Universe Harry Potter dengan Genre Homoseksual di Twitter - Dhiah Indriani, Laillia (Calathu: Jurnal Ilmu Komunikasi, 2024)
Understanding the diversity of sexuality is still taboo in Indonesia. This directly leads to the practice of marginalising groups with homosexual sexual orientation. Those who have homosexual tendencies cannot freely express themselves, both in the virtual and real worlds. This hegemony of heteronormativity then began to receive a kind of counter-hegemony from various parties, one of which was from the writers and readers of the Alternative Universe (hereinafter referred to as AU) Harry Potter on Twitter. Harry Potter itself is a fictional story with the theme of the wizarding world written by J.K. Rowling, which is often reproduced by fans through various media; AU is one of them. Through AU, fans can imagine creating their own stories using the characters in the Harry Potter story series. One of the highlights of this AU version is when fans make the people in the Harry Potter characters homosexual. Not only does it involve fantasy and imagination, fans also pay attention to their personal identity when interacting with homosexual stories. This study aims to find out how writers and readers of Harry Potter AU stories on Twitter play out homosexual fantasies, as well as how privacy management is used to feel safe interacting with homosexual subjects. To answer these questions, the author conducted research using the netnography method on Twitter. In the process, the author not only looked at user interactions on each Harry Potter AU story but also distributed questionnaires and interviews to the author and readers of the AU story. As for data analysis, the author uses the concept of schizoanalysis from Deleuze and Guattari and combines it with Sandra Petronio's communication privacy management theory. The results of this study show that writers and readers of Harry Potter AUs with homosexual characters have a tendency to want to hide their personal information. They do not want to be recognised when interacting with homosexual stories, even though they are actually very interested in them. This is partly due to social pressure that still upholds heteronormativity.